STUDY OF SOCIO-ECONOMIC CONDITIONS FARMERS CLOVES IN GOISOOINAN VILLAGE SIPORA UTARA DISTRICT KEPULAUAN MENTAWAI REGION - SUSANA, EFRIDAS; Juita, S.Pd. M.Si, Erna; Prari Keslan, Rozana Eka (Pendidikan Geografi, 2014)
ABSTRACTÂ Â This study aimed to obtain the data, analyze and discuss the socio-economic conditions Farmers Cloves in Goisooinan Village Sipora Utara District Kepulauan Mentawai Region. This type of research is classified as descriptive. Population is the entire population of the Goisooinan village are 1.035 with 212 head of family. Samples were taken in two ways, the samples were taken with the area proportional random sampling technique, namely Pogari, Atduru, Kaliou each with a proportion of 50 % of the sample size of the number of families representing 86 families (KK) data was collected using a questionnaire guided analysis used is Descriptive statistics using percentage formula. The results showed as follows; (1) Revenue clove farmers in Goisooinan Village Sipora Utara District Kepulauan Mentawai Region generally Rp 1.000.000/month, condition good income in the year 2013, on the side of Rp 1.000.000, income of other family members of the wifes income and number of family members Rp 1.000.000, (2) the condition of education of clove farmers in Goisooinan Village Sipora Utara District Kepulauan Mentawai Region are generally complete primary school, generally the wife finished primary school, elementary school children generally 1, junior high school children generally 1, child the high school is generally one person, and generally there are no dropouts. Children mostly around the residence and source of the family s own educational expenses, (3) health condition clove farmers in Goisooinan Village Sipora Utara District Kepulauan Mentawai Region, a good physical health condition, type of illness usually fever, the treatment is a health center, general hospital distance of 20 km from the house and family members in the year 2013 is generally a mild illness, (4) housing conditions clove farmers in Goisooinan Village Sipora Utara District Kepulauan Mentawai Region, building area > 8,7 m, the condition of the building semi-permanent houses 50%, number of bedrooms generally 4 rooms , number of bathrooms and number is 1 piece 1 piece of kitchen space generally and (5) social relations social clove farmers in Goisooinan Village Sipora Utara District Kepulauan Mentawai Region including quite wellÂ